Pedagogical trade as a means of didactic training of primary school teachers (Pedagogy of Higher and Secondary Education, 2014)
Razmolodchikova I. V. Pedagogical trade as a means of didactic training of primary school teachers.This article provides guidelines in usage of pedagogical trades (situations) as means of organization academic and research work of future teachers of primary school. The meaning of concepts are «task», «pedagogical task», «educational situation». Classification of educational pedagogical tasks, which were shown, are desirable to use in the initial phase of the specialists' training quality.
Keywords: pedagogical trade; didactic tool; process of learning; professional preparing; teacher of primary school